Instructional design process in a web-based learning management system: design, implementation and evaluation issues - Njenga, James Kariuki (University of the Western Cape, 2013)
Magister Commercii (Information Management) - MCom(IM) === Web technologies have necessitated a transformation culture in higher education institutions. Many of these institutions are employing web technologies whose development, for varying reasons, is not supported by research in their field and domain of use. One such field is instructional design for the web learning. Although there is a lot of research on the most effective instructional design strategies, the use of research for web-based learning applications has been limited. This thesis reports on a study aimed at transforming the research on instructional design into practice by designing an instructional design system and providing an argument for its implementation. The argument is intended to facilitate the design and development of an instructional design subsystem of the web, that would in turn offer effective and efficient ways for creating web-based learning materials to instructors. The study started by examining the various paradigms, theories and practices of instructional design with the intent of using them to enrich and improve the practice of instructional design in web learning. It undertook a thorough and systematic review of the literature on instructional design in order to come up with an instructional design system. The design approach used successful design patterns that have been used elsewhere, e.g. in software design, to create common responses or solutions to recurrent problems and circumstances. Instructional design patterns were identified in this study as the recurrent problems or processes instructional designers go through while creating instructional materials, whose solutions can be reused over and over again. This study used an iterative developmental research process of finding and modelling an instructional design process as the research methodology. This process follows and builds on existing research on instructional models, theories and strategies, and ensures that the same methodology can be used to test the theories in the design, thus improving both the research and the design. === South Africa